Analysis of the Potential Use of Graphene Oxide Nanoparticles in the Field of Materials: Bibliometric Analysis - Chairul Islam, Sultan Nazmi (Journal of Scientech Research and Development, 2023)
This research was carried out to present bibliometric analysis which can be useful for mapping ongoing research topics and trends, especially in the topic of the use of graphene oxide in the materials field, so that it is hoped that it can help further research that will be carried out. The research method used is descriptive qualitative with bibliometric analysis using VOSviewer to visualize related research terms. Data collection was carried out using the publish and publish application using the keywords graphene oxide, nanoparticles, and materials with a time span of 2017 to 2023. The research results showed that there were fluctuations in the number of research conducted each year on the topic of graphene oxide.